Qualitative study of satisfaction with physiotherapy care of individuals with low back pain at a tertiary hospital in Nigeria: Implication for Patients education on low back pain and expectation of care (African Journal of Biomedical Research, 2024)
Physiotherapists are leading providers of care for patients with low back pain, a condition with severe economic burden in Nigeria. The satisfaction of patients is an essential indicator of the quality of such care. This study investigated patients' satisfaction with physiotherapy care for low back pain at a tertiary hospital in Nigeria. To explore their satisfaction with physiotherapy care, we conducted qualitative research among patients with LBP receiving treatment at the Out-patient Physiotherapy Clinic of a tertiary hospital in Nigeria. Using the purposive sampling technique, 14 patients (eight females, six males) were recruited for focus group discussion (FGD). Content thematic analysis was used for data analysis; the data was reduced by identifying categories and themes, data check and validation was done. Three themes emerged from the qualitative study: relationship with the physiotherapist, adequacy of treatment, and factors influencing satisfaction. It was established that there was a cordial relationship between physiotherapists and patients, and treatment was perceived to be adequate. However, the following factors were perceived as influencing satisfaction with care negatively; inadequate equipment and supplies, language barrier at the reception for non-Yoruba speaking patients, prolonged waiting time before treatment, insufficient human resources and cost of care. Patients were satisfied with physiotherapy care for LBP they received at the out-patient physiotherapy clinic. Treatment was perceived to be adequate. Surprisingly, patients have little or no knowledge of physiotherapy care for LBP and thus no specific expectation of care. Therefore, patient education is pivotal and should be part of management in Physiotherapy clinics.